2014
DOI: 10.1007/s00405-014-3065-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous tumours of the head and neck: a spectrum of biological behaviour

Abstract: Lipomatous tumours are rare in the head and neck region. Their biological behaviour varies greatly, from absolutely benign to histologically benign but locally infiltrative and, finally, invasive with metastatic potential. Each lipomatous tumour has to be treated accordingly. It is of paramount importance before eventual surgery is planned to perform adequate imaging, diagnostic biopsy and careful assessment. Only in small (<5 cm), superficial soft tissue tumours or when magnetic resonance imaging has demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 116 publications
0
17
0
Order By: Relevance
“…Davis 12 and Dubin 22 pointed out a possible role of adjuvant radiation therapy (RT) in reducing the rate of local recurrences. However, the effectiveness of adjuvant RT in treating liposarcomas and DDL in particular, is still controversial; several studies showed as adjuvant radiotherapy reduces the rate of local recurrence from 60% to 40%, but it does not modify the overall survival or the rate of metastasis 1, 2, 5. In our case adjuvant radiotherapy was warranted because of the aggressive histology pattern (high grade rabdo-myosarcoma and pleomorphic sarcoma) and the inability to obtain a wide resection margin.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Davis 12 and Dubin 22 pointed out a possible role of adjuvant radiation therapy (RT) in reducing the rate of local recurrences. However, the effectiveness of adjuvant RT in treating liposarcomas and DDL in particular, is still controversial; several studies showed as adjuvant radiotherapy reduces the rate of local recurrence from 60% to 40%, but it does not modify the overall survival or the rate of metastasis 1, 2, 5. In our case adjuvant radiotherapy was warranted because of the aggressive histology pattern (high grade rabdo-myosarcoma and pleomorphic sarcoma) and the inability to obtain a wide resection margin.…”
Section: Discussionmentioning
confidence: 74%
“…Sarcomas of the head and neck region represent rare pathology in adults (accounting for 2–10% of all cancers), while they are more frequent in the pediatric population (35%) 1, 2. Head and neck liposarcomas (HNLS) account for less than 5% of liposarcomas 3 and 2–9% of all sarcomas arising in the region 4, 5, 6, 7, 8, 9, 10, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although indeed in some cases of lipomatous tumors cytogenetic analysis might be helpful in their differential diagnosis, it is definitely not a standard procedure in cases in which the histological diagnosis is not in doubt [2,3]. Moreover, cytogenetic analysis is of limited value in the case of spindle cell lipoma.…”
Section: Dear Editormentioning
confidence: 99%